การควบคุมการใช้อำนาจของแพทยสภาโดยศาลปกครอง - อโณทัย ศรีสมัย (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To study the nature of exercising administrative power of the Medical Council in relation to the control of medical professional performing, the type and scope of the control of legitimacy of such exercise of power by the Administrative Court. Meanwhile it is provided to compare this issue with the foreign countries namely England and France and analyze with emphasis the judgments. According to the study, it has been found that the control of the legitimacy on exercising administrative power of the Medical Council by the Administrative Court of Thailand, the Administrative Jurisdiction of France as well as the High Court of Justice of England. The judicial organ has the power to control and examine the legitimacy of administrative actions taken by the Medical Council such as in relation to the issuance of rules, administrative orders or the adjudications of cases related to the violation of principles of medical ethics (or called "acte judiciaire" (Judicial Act) in France). However, there are some different interesting points of the judgments in each country. For example, in France, this type of case shall be submitted directly to Conseil d’Etat or the Council of State (equivalent to the Supreme Administrative Court of Thailand). In fact, it is determined that only the matters of law shall be submitted to the court. This idea is arisen from the fact that in case where a dispute is considered by the approval of the organ in charged of the trial and adjudication of disputes including the qualified persons from the medical and legal field, it means that this matter of fact is unanimously accepted by the persons with high qualifications and expertise. In this regard, the trial and adjudication has been performed in a swift and relevant manner to the principle of authority delegation to professional bodies to control and examine between themselves. Obviously, the judicial organ has the power only to examine and control the matters of law. Accordingly, in conformity with the principle of the Rule of Law and the separation of powers, the researcher would like to propose some amendments of the rules on this matter similarly in France.